إيجاد اتجاه جديد: تحليل منهج اللغة العربية في بيت الحفظ القرآن الكريم بين التحديات والفرص والتطور - Muhammad Ridwan; Wahyuni Wahyuni ('ARABIYYA: JURNAL STUDI BAHASA ARAB, 2025)
This study investigates the state and development of the Arabic language curriculum at Rumah Tahfidz, with a particular emphasis on the integration of Al-Qur'an memorisation and vocabulary comprehension.  Observations and interviews with teachers and administrators indicate that the current curriculum is still undocumented and informal. Furthermore, without systematic guidelines, learning emphasises mechanical memorisation.  To ensure that students can not only memorise verses but also understand the vocabulary of the Qur'an, it is necessary to develop an integrative curriculum that combines linguistic understanding with verse memorisation.  The use of educational digital media such as Think Qur'an, interactive flash cards, and short videos that increase teacher motivation and engagement opens up further opportunities for development. The next focus of development is to create a simple contextual mini-curriculum, using Qur'anic vocabulary, and equipped with simple evaluations in the form of short dialogues or word meaning quizzes.  This study provides the basis for developing a flexible, organised, and meaningful Arabic language curriculum model for Rumah Tahfidz. This model will support the achievement of educational objectives that include memorising and understanding the content of the Qur'an in context.